Prismatomeris glabra: ergogenic effects and sexual function in mice / Razali Mohamed Salleh - Mohamed Salleh, Razali (Institute of Graduate Studies, UiTM, 2016)
A decoction of the roots of Prismatomeris glabra (PG), family Rubiaceae, has been traditionally used by rural people for wellness, improvement of stamina and for aphrodisiac effects. However there were no scientific data to support the folkloric use of this plant. This research was thus conducted to determine whether aqueous extract of P. glabra roots possess antioxidant capacity, produce ergogenic effects and improve sexual function. Toxicity studies were performed to estimate safety for human consumption. PG extract was prepared by boiling powdered roots for 10 minutes before drying in spray dryer. Toxicity studies in mice were conducted for acute, subacute and subchronic effects. OECD guidelines were used for 14-day observation following acute dose given to male and female mice intraperitoneally. In all experiments, age-matched control mice were given normal saline. Gross necropsy, hematology and biochemistry analyses were conducted following killing. Toxicity studies in vitro were conducted using selected cell lines. Antioxidant capacity was determined in vitro and in vivo using established methods. Ergogenic effects were studied in weight-bearing mice performing forced swim test (FST) to exhaustion following treatment with 500 mg/kg/d p.o. PG. Mice were killed immediately after the final FST for blood biomarker assays. Castrated/non-castrated mice were used to determine the effect of PG (500 mg/kg/d p.o.) on testosterone levels…